PERAN INTERVENSI SOSIAL DALAM MEMULIHKAN TRAUMA ANAK PASCA BENCANA ALAM - Artika Cesar Aura Devi; Putri Fairuz, Nurul Janah, Vina Andani Peni Sanga, Zahra Permata Sari, Tugimin Supriyadi (ADISAM PUBLISHER, 2024)
Indonesia is a country that is very vulnerable to natural disasters due to its geographical location and climate conditions. Natural disasters not only cause physical losses, but also psychological trauma, especially in children who do not yet have the cognitive ability to understand the situation. This study aims to explain the role of social intervention in recovering children's trauma after a natural disaster. The method used is a literature study by analyzing various scientific articles related to social intervention and trauma healing in children. The results of the study showed that trauma healing programs based on play therapy, environmental education, and traditional games have proven effective in helping children overcome anxiety and increase their enthusiasm to return to normal life